2016
DOI: 10.1093/nar/gkw763
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide co-localization of active EGFR and downstream ERK pathway kinases mirrors mitogen-inducible RNA polymerase 2 genomic occupancy

Abstract: Genome-wide mechanisms that coordinate expression of subsets of functionally related genes are largely unknown. Recent studies show that receptor tyrosine kinases and components of signal transduction cascades including the extracellular signal-regulated protein kinase (ERK), once thought to act predominantly in the vicinity of plasma membrane and in the cytoplasm, can be recruited to chromatin encompassing transcribed genes. Genome-wide distribution of these transducers and their relationship to transcribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 78 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…Gardini et al elegantly demonstrated the importance of Integrator and SEC for productive elongation of genes such as JUN , FOS , CCNL1 , NR4A1 8 . Mikula et al neatly showed the genomic occupancies of nEGFR at EGR1 and FOS genes using ChIP-seq analysis 5 . To our knowledge, there is no study yet analyzing the genomic distribution of nEGFR, RNAPII, Integrator and SEC altogether to identify nEGFR target genes undergoing productive elongation after EGFR induction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gardini et al elegantly demonstrated the importance of Integrator and SEC for productive elongation of genes such as JUN , FOS , CCNL1 , NR4A1 8 . Mikula et al neatly showed the genomic occupancies of nEGFR at EGR1 and FOS genes using ChIP-seq analysis 5 . To our knowledge, there is no study yet analyzing the genomic distribution of nEGFR, RNAPII, Integrator and SEC altogether to identify nEGFR target genes undergoing productive elongation after EGFR induction.…”
Section: Resultsmentioning
confidence: 99%
“…The gene transactivation regulation of nEGFR has been investigated by comparing the chromatin recruitment between nEGFR and RNAPII after EGF stimulation in HeLa cells 5 . However, because RNAPII pausing happens during the initial phases of elongation, the chromatin recruitment of RNAPII alone is insufficient for productive transcription elongation 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Meisel Sharon S et al [20] showed that AP2M1 serves a mechanistic role in insulin-like growth factor-1 receptor internalization. Mikula et al [31] reported that AP2M1 is essential for the recruitment of receptor tyrosine kinases and components of signal transduction cascades to chromatin containing genes which are transcribed. In addition, some studies have preliminarily explored the mechanisms of AP2M1.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond affecting termination factor recruitment, what aspects of Tyr1 phosphorylation and Slt2 function are transferable to mammalian cells? Evidence that Slt2 is present with RNAP II on transcribed genes and homologs Erk1/2 are recruited to genes in a manner similar to Slt2 83,84 has been reported, but might one of these kinases, or a related one, have Tyr1P activity? Future studies will continue to describe the many intricacies of the CTD and discover new aspects of regulation, but now that the "orphans" are orphans no longer, continued comparison across organisms will prove enlightening.…”
Section: Discussionmentioning
confidence: 99%